A Bibliometric Analysis of Inclusive Education in Indonesia: Achievement and its Relations to General Education - Dianastiti, Firstya Evi; Suwandi, Sarwiji; Setiawan, Budhi (INKLUSI, 2024)
This bibliometric analysis study used Vosviewer application as a data processor. Data sources in the form of research articles were collected from Dimension.ai using the keyword "inclusive education". Research data screening was carried out by the PRISMA method. The results of data analysis indicated that research on inclusive education in Indonesia from 2012 to 2022 showed an increasing trend. In the analysis of network visualization, data were divided into 4 main clusters, with keywords “teacher” and “need” came as the highest terms. Then in the overlay visualization it is known that the latest topics that are being studied are related to keywords of barriers, special needs, methods, disability, children, infrastructure, facilities, and obstacle. As for the analysis of density visualization; the keywords are attitude, handling, and depth interviews are in dark clusters so that it can be concluded that novelty research can be carried out on these topics as well as on topics that have not appeared in mapping. The results of the bibliometric and discussion concluded that research on inclusive education and general education on the topic of appropriate ICT-based learning strategies and media is needed to maximize the potential of students with disabilities in the learning process.